Optimising the fronthaul connectivity and backhaul utilization via DWDM using BTS Hotel Concept / Mohd Yusdee Yusoff … [et al.] - Yusoff, Mohd Yusdee; Mohammad, Mohammad Yazid; Sarnin, Suzi Seroja; Naim, Nani Fadzlina (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
The research proposal will be focusing on the benefit for Mobile Network Operators (MNOs) in the backhaul connectivity. In normal situation, each of Base Transceiver Station (BTS) will need to carry their backhaul using any Transmission link either Microwave, Fiber or VSAT to be connected to the Core Network to establish a complete cycle of connectivity in Mobile Network. This backhaul will carry an individual link of each BTS (end site) site that is depends on number of hub before it reach to the Core Network. By introducing the Backhaul Grooming using BTS Hotel Concept will benefit MNOs in cost reduction on numbers of hub/link towards reaching the Core Network. Besides, the solution is economical where the BTS site footprint and Power Consumption will be reduced. The solution will be using the DWDM concept via Fiber optics network where multiple BTS sites will be connected and groom in One location so called BTS Hotel. In this BTS Hotel, the Baseband Unit (BBU) of NodeB/eNodeB will be placed in rack while the Remote Radio Unit (RRU) will remain at End site/station. The connection between BBU and RRUs is called Fronthaul and the connection will be grooming using Dense Wave-length Division Multiplexing (DWDM) connectivity.Using this solution, multiple End Sites will be connected to one single point called BTS Hotel and from this Hotel/room the Backhaul connection to the Core Network or Evolved Packet Core (of each Telco) will be only ONE Single connection instead off multiple link-up from each End site where this solution is very economical as compared to conventional method that currently practice in the industry. The fronthaul connectivity is monitored by the MNOs monitoring center as the RRUs and BBU monitored via NMS (Network Monitoring System) while the backhaul connectivity and utilization will be then monitored via the backhaul usage and can be upgraded accordingly when there is a need subject to site utilization.